Genetic Relationship Assessment of Vanda Using HAT-RAPD Technique - Thanananta, Narumol; Atiphongarporn, Eakwit; Thanananta, Theerachai (Thai Journal of Science and Technology, 2024)
The Vanda is the second most important commercial orchid after the Dendrobium. There are many species and hybrids, making it difficult to classify by morphology and easily confused. High annealing temperature-random amplified polymorphic DNA (HAT-RAPD) technique was used to identify 12 samples of Vanda. The total 72 random primer were screened and 30 primers could be used for DNA amplification. 18 primers were selected and used to analyze all the DNA samples. Total 211 bands were detected, of which 206 were gave different DNA fingerprinting and all cultivars were clearly differentiated by using 14 primers. A dendrogram constructed based on polymorphic bands showed genetic similarities among Vanda each cultivar with similarity coefficients ranging 0.37-0.69. The HAT-RAPD markers developed can be used to identify Vanda cultivar and plan to breeding program.